In this issue we read other voices from Brazil: Lemos outras vozes do Brasil nesta edição - Farias, Miguel (Árboles y Rizomas, 2022)
The editor introduces issue number 2, volume 4 of the journal, describes the locus of enunciation at the moment of preparing to launch this issue, and offers a description and synthesis of its contents. He highlights the participation of Brazilian researchers in this issue of the journal.